Implementing The CALLA Framework And Metacognitive Approach To Overcome Difficulties In Mastering Arabic Vocabulary - Nadiah Abd Rahim; Nadhilah Abdul Pisal; Ummi Syarah Ismail; Nurazan Mohd Rouyan (Ijaz Arabi Journal of Arabic Learning, 2026)
The issue of Arabic vocabulary mastery has long been a concern among researchers and educators. In Malaysia, students’ limited proficiency in Arabic vocabulary remains a persistent challenge across both school and higher education settings. Two primary shortcomings have been identified in the teaching and learning of Arabic vocabulary: (1) the lack of explicit implementation of vocabulary learning strategy training, and (2) insufficient exposure to effective vocabulary learning strategies. This paper aims to examine the challenges faced by Malaysian students in mastering Arabic vocabulary and to explore how the Cognitive Academic Language Learning Approach (CALLA) and metacognitive approach can serve as effective interventions, based on secondary sources. Students who receive explicit instruction in vocabulary learning strategies are more likely to develop greater metacognitive awareness in selecting and applying appropriate strategies, thereby improving their ability to self-regulate and manage the vocabulary learning process effectively. This paper contributes to a deeper understanding of effective vocabulary instruction strategies and offers pedagogical implications for enhancing comprehension and reducing learner errors in Arabic vocabulary learning.